PHILOSOPHICAL REFLECTIONS ON THE LIMITATIONS OF CONVENTIONAL MEDICINE - JOHNSTON, BRUCE; S. LAURA, PROFESSOR RONALD (IJRDO - Journal of Social Science and Humanities Research, 2017)
The central objective of this paper is to show that although contemporary western medicine represents a valuable approach to health, it lamentably remains an incomplete framework within which the achievement of its goals can be realised. In what follows we shall thus endeavour to establish that the philosophical presumptions underpinning the [western] medical-industrial complex in dealing with many modern day health problems are fundamentally misguided. Moreover, we shall argue that in certain contexts there has been both a misuse and abuse ofits position ofinstitutional power. This being so, we shall see that Medical Science, especially in regard to its liaison with the pharmaceutical industry, has been corrupted in the pursuit ofprofit, leaving the interests of people’s health largely in the hands ofthe medical drug industry. Lest we be misunderstood, let us make clear that we make no pretence of denigrating the importance of conventional medicine and its quite remarkable achievements, though this is not to say that the dominant materialist foundations of the methodological approach to advancing community health represent a sufficient description of the wide array of our health problems. Our argument is that although Conventional Medicine is an extremely valuable orientation to our current health problems, it remains an incomplete paradigm ofhealing in regard to chronic and degenerative diseases such as cancer an diabetes.